microRNA-20a Inhibits Autophagic Process by Targeting ATG7 and ATG16L1 and Favors Mycobacterial Survival in Macrophage Cells - Guo, Le; Zhao, Jin; Qu, Yuliang; Yin, Runting; Gao, Qian; Ding, Shuqin; Zhang, Ying; Wei, Jun; Xu, Guangxian (Frontiers in Cellular and Infection Microbiology, 2016)
Autophagy plays important roles in the host immune response against mycobacterial infection. Mycobacterium tuberculosis (M. tuberculosis) can live in macrophages owing to its ability to evade attacks by regulating autophagic response. MicroRNAs (miRNAs) are small noncoding, endogenously encoded RNA which plays critical roles in precise regulation of macrophage functions. Whether miRNAs specifically influence the activation of macrophage autophagy during M. tuberculosis infection are largely unknown. In this study, we demonstrate that BCG infection of macrophages resulted in enhanced expression of miRNA-20a, which inhibits autophagic process by targeting ATG7 and ATG16L1 and promotes BCG survival in macrophages. Forced overexpression of miR-20a decreased the expression levels of LC3-II and the number of LC3 puncta in macrophages, and promoted BCG survival in macrophages, while transfection with miR-20a inhibitor had the opposite effect. Moreover, the inhibitory effect of miR-20a on autophagy was further confimed by transmission electron microscopy (TEM) analysis. Quantification of autophagosomes per cellular cross-section revealed a significant reduction upon transfection with miR-20a mimic, but transfection with miR-20a inhibitor increased the number of autophagosomes per cellular cross-section. Moreover, silencing of ATG7 significantly inhibited autophagic response, and transfection with ATG7 siRNA plus miR-20a mimic could further decrease autophagic response. Collectively, our data reveal that miR-20a inhibits autophagic response and promotes BCG survival in macrophages by targeting ATG7 and ATG16L1, which may have implications for a better understanding of pathogenesis of M. tuberculosis infection.